Haploid Induction of Kenaf (Hibiscus Cannabinus L.), Okra (Abelmoschus esculentus L.) and Spring Onion (Allium fistulosum L.) using Anther, Ovary and Ovule Cultures - Ahmed Mahmood Ibrahim (2016)
The production of haploid plants by anther and ovary cultures followed by chromosome doubling can produce homozygous parent lines in a relatively shorter time compared to the production of inbred lines by conventional method through repeated selfings. The thesis describes the studies undertaken to investigate the potential of anther, microspores (pollens), ovary and ovule cultures of kenaf (Hibiscus cannabinus L.), okra (Abelmoschus esculentus L.) and spring onion (Allium fistulosum L.) for the production of haploid plants. Anther, ovary and ovule were excised from flower buds at different stages. The ability to produce haploid callus or somatic embryogenesis and thereby regenerate into haploid plants were investigated. Several factors such as flower buds initiation time, type of media, plant growth regulator (PGR) combinations and concentration, sucrose concentration and dark periods have been evaluated. The flower buds of different sizes were dissected to determine their stage of development before subjected to various pretreatments (cold and colchicines) and then the anthers, microspores, ovaries and ovules were cultured on different PGR combinations (NAA, IAA, 2,4-D, KIN, BAP, IBA, ZTN, 2iP and TDZ) and concentrations. The cultures were incubated in both dark and light condition. The suitable developmental stage of microspore for callus induction was obtained from 8 mm length of flower buds in kenaf and 12 mm length of flower bud in okra from the first batch flower emergence and 2 mm length flower bud in spring onion. While the suitable developmental stage for ovaries and ovules were one or two days before anthesis of kenaf and okra and and 3-5 mm flower bud in spring onion. Haploid calli and root were produced from the anther, ovary and ovule of kenaf and okra. Regeneration of haploid plantlets could be obtained in spring onion using flower and ovary cultures which were confirmed by ploidy test using a flow cytometry. The results of the study revealed that the effect of flower bud initiation time was an important factor in anther and ovary cultures. There were no significant difference in percentage of callus induction on cold pre treatment, 0.5 mg/l TDZ or 3.0 mg/l BAP combined with 2.0 mg/l NAA gave highest percentage (95%) of callus induction. Among the three callus induction media, MS medium was the most responsive medium with an average of 95% callus induction. A significant differences were observed at 3% of sucrose concentration on callus induction. Incubation in a dark place for 28 days in dark place gave highest percentage (92.5%) of callus and root induction. No shoot was developed from kenaf and okra despite several treatments and further sub-culturing. The study can be starting point for the improvement of the three crops. The protocols developed for the production of haploid plantlets in spring onion helpful in a breeding program for the improvement of genetic traits of spring onion.